Virtual Reality sebagai Media Pembelajaran Interaktif pada Materi Tata Surya: Solusi Edukasi Modern di Era Pendidikan 5.0 - Rohmah, Labibah; Shahhilina, Dina Surya; Wijaya, Danar Putra (Jurnal Informatika & Teknologi Cerdas, 2025)
This research uses the literature study method to examine the utilization of Virtual Reality (VR) technology as an interactive learning media on solar system material in the context of the Education 5.0 era. Data were collected from Google Scholar and SINTA database with a focus on scientific journals and proceedings in the last five years. The literature selection process was carried out through abstract analysis, methods, and conclusions to ensure the relevance and accuracy of the information. The results of the study show that VR is able to present three-dimensional visualizations that are immersive and interactive, thus increasing the engagement and effectiveness of learning solar system material significantly compared to conventional methods. The use of VR as a modern educational solution not only facilitates understanding of complex concepts, but also increases student motivation and learning experience. The implementation of VR in learning solar system material requires the support of special devices such as devices with gyroscope features or VR boxes to be optimally used in an adaptive and innovative educational environment. Keywords: Virtual Reality, Interactive Learning Media, Solar System Material, 5.0 Education, Learning Effectiveness.